RESPON GURU DAN SISWA SEKOLAH DASAR TERHADAP HASIL PENGEMBANGAN SOAL ONLINE MENGGUNAKAN GOOGLE FORM SEBAGAI IMPLEMENTASI BELAJAR DARI RUMAH - Kartono Kartono (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
In the era of the COVID-19 pandemic and the 21st century digital era, it is very necessary to have questions that can be used online that are validated and ready to be used to assess the learning process that has been carried out, so online question development research is carried out using google form in learning Theme 3 Class V Elementary Schools as an implementation of Learning from Home (BDR) to reduce the spread of COVID-19. The research approach used to develop online questions using google form is a mixed method approach because the research carried out is classified as research and development or R&D research. The data collection technique is to answer the sub-problem formulation regarding the response of the teacher in using the results of the trial for developing online learning questions Theme 3 Class V Elementary Schools which are distributed via google form and student responses when working on the results of developing online learning questions Theme 3 Class V Elementary Schools in google form is an open interview with the teacher and provides a closed questionnaire to students. The results obtained were that the teacher gave a positive response regarding the use of the results of developing online learning questions for Theme 3 Class V Elementary Schools which were distributed through Google Form and students gave very good responses when working on the results of developing online learning questions Theme 3 Class V Elementary School on google form. Abstrak Pada era pandemi COVID-19 dan era digital abad 21 sangat diperlukan ketersediaan soal yang dapat digunakan secara online yang tervalidasi dan siap digunakan untuk menilai proses pembelajaran yang telah dilakukan, maka dilakukan penelitian pengembangan soal online menggunakan google form pada pembelajaran Tema 3 Kelas V Sekolah Dasar sebagai implementasi Belajar dari Rumah (BDR) untuk memutus penyebaran COVID-19. Pendekatan penelitian yang digunakan untuk mengembangkan soal online menggunakan google form ini adalah pendekatan mixed method dikarenakan penelitian yang dilakukan tergolong penelitian research and development atau R&D. Adapun teknik pengumpulan data untuk menjawab sub rumusan masalah mengenai respon guru dalam menggunakan hasil uji coba pengembangan soal online pembelajaran Tema 3 Kelas V Sekolah Dasar yang di sebarkan melalui google form dan respon siswa ketika mengerjakan hasil pengembangan soal online pembelajaran Tema 3 Kelas V Sekolah Dasar di google form adalah wawancara terbuka kepada guru dan memberikan angket tertutup kepada siswa. Adapun hasil yang di peroleh yaitu guru memberikan respon yang positif mengenai penggunaan hasil pengembangan soal online pembelajaran Tema 3 Kelas V Sekolah Dasar yang di sebarkan melalui google form serta siswa memberikan tanggapan yang sangat baik ketika mengerjakan hasil pengembangan soal online pembelajaran Tema 3 Kelas V Sekolah Dasar di google form.